FRI0512 Apremilast, an oral phosphodiesterase 4 inhibitor, is associated with long-term (156-week) improvements in basdai in psoriatic arthritis patients: pooled results from 3 phase iii, randomized, controlled trials. (15th June 2017) - Mease, PJ; Marzo-Ortega, H; Poder, A; Bosch, F Van den; Wollenhaupt, J; Lespessailles, E; McIlraith, M; Teng, L; Hall, S
Abstract : Background: In PALACE psoriatic arthritis (PsA) studies, the Bath Ankylosing Spondylitis Disease Activity Index score (BASDAI) was used as an exploratory measure in a subset of patients (pts) considered by investigators to have axial involvement, although PsA spondylitis was not confirmed by imaging. Objectives: Report the impact of apremilast 30 mg BID (APR) treatment on BASDAI over 156 wks using pooled PALACE 1–3 data of pts with active PsA despite prior conventional DMARDs and/or biologics. Methods: APR treatment outcomes were evaluated in a subset of pts with baseline (BL) BASDAI ≥4 ("subset") over 156 wks. Results: BL BASDAI ≥4 was reported for 454/1493 (30%) pts. Mean PsA duration was similar between the subset and rest of the PALACE 1–3 population (n=1039); mean BL psoriasis body surface area (BSA) and percentage of pts with BSA ≥3% were slightly higher. The subset had higher mean BL values vs the rest of PALACE 1–3 pts for C-reactive protein (1.12 vs 0.93), pain VAS (63.6 vs 53.8 mm), pt's global assessment of disease activity (62.2 vs 53.5 mm), and physician's global assessment of disease activity (PhGA; 59.0 vs 53.0 mm) and markedly worse mean HAQ-DI (1.41 vs 1.08), SF-36v2 Physical Functioning (30.6 vs 35.8), and FACIT-F (25.7 vs 31.8) scores. Despite disease activity differences, BL concomitant oral DMARDs were similar in both groups: 1 DMARD in 61.0% (subset) vs 57.8% (rest of PALACE 1–3 pts); methotrexate was the most common DMARD. In the subset, 73.6% had been treated with only oral DMARDs prestudy (44.9% with only 1); 25.1% had prior biologic use. Mean BL BASDAI in the subset was 6.6 with APR and 6.4 with placebo (PBO). Mean BL BASDAI question 2 score, referring directly to spinal and hip pain, was 6.7. APR resulted in greater mean improvement in BASDAI vs PBO at Wk 16 (−1.53 vs −0.91; P =0.0173) and Wk 24 (Table). As early as Wk 16, a 19% mean decrease in the question 2 score was seen with APR vs an increase with PBO. Other disease measures significantly improved early in treatment, including HAQ-DI, fatigue, PhGA, and mPsARC (Table). Long-term improvement was seen across measures, with mean BASDAI reductions of 2.18 at Wk 52 and 2.19 at Wk 156 (Table) and question 2 reductions of 1.94 and 2.28, respectively; treatment resulted in a shift toward lower BASDAI across the subset, with a significant proportion reaching BASDAI <4. Conclusions: In this post hoc analysis of pooled data, pts reporting BASDAI ≥4 at BL appear to experience greater disease burden, including disability, pain, and fatigue; effective treatment strategies may not have been available. APR treatment resulted in long-term improvements in BASDAI and other measures in pts with clinically suspected axial disease. Disclosure of Interest: P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, H. Marzo-Ortega: None declared, A. Poder: None declared, F. Van den Bosch Consultant for: AbbVie, Celgene Corporation, Merck, Pfizer, UCB, Janssen, J. Wollenhaupt Grant/research support from: Abbott, BMS, MSD, Pfizer, UCB, Consultant for: Abbott, BMS, MSD, Pfizer, UCB, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, Servier, M. McIlraith Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, S. Hall Consultant for: Boehringer Ingelheim, MSD, Roche, Schering-Plough, Servier, Wyeth, Paid instructor for: Amgen, AstraZeneca, Boehringer Ingelheim, Centocor, GSK, MSD, Pfizer, Sanofi Aventis, Sanofi Pasteur, Schering-Plough, Serono, Wyeth, Speakers bureau: Boehringer Ingelheim, GSK, MSD, Pfizer, Roche, Sanofi Aventis, Schering-Plough, Wyeth